ADDRESS TO THE IMAGE OF LAYLI IN THE GHAZALIYAT OF TURKISH POETS CREATED IN THE ENVIRONMENT OF BUKHARA - Ulug'murodova Kamola Murodullayevna (Western European Studies, 2025)
This article explains the use and content of the image of Layla in the works of poets who worked in the Bukhara emirate. It also analyzes the genres in which the image was used, its spiritual and aesthetic image, the artistic ideas expressed through it, the exaltation of the image of a woman, and its combination with mystical concepts.
Keywords: Layla; Majnun; Bukhara; creator